THE ROLE OF CLOUD-BASED TOOLS IN MODERN CYBERCRIME INVESTIGATIONS: INSIGHTS FROM A RANSOMWARE CASE STUDY - Arvind Kumar Akula (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article examines the application of cloud-based digital forensics techniques in investigating a ransomware attack on a company's cloud storage infrastructure. Through a comprehensive case study approach, we explore how cloud computing capabilities enhance the forensic process, focusing on scalable data processing, collaborative investigation methods, and the utilization of cloud-native forensic tools. The article demonstrates that cloud-based forensics significantly improves the efficiency and effectiveness of ransomware investigations by enabling rapid analysis of massive datasets, facilitating real-time collaboration among geographically dispersed investigators, and providing robust evidence preservation mechanisms. Our findings reveal that cloud-native forensic tools, coupled with advanced network traffic analysis techniques, offer unique advantages in identifying attack vectors and preserving the integrity of digital evidence. This article contributes to the growing body of knowledge on cloud forensics and provides practical insights for cybersecurity professionals dealing with complex ransomware incidents in cloud environments. The results underscore the importance of adapting traditional forensic methodologies to leverage the full potential of cloud computing in addressing the challenges posed by sophisticated cyber threats.